2016
DOI: 10.1089/apc.2015.0333
|View full text |Cite|
|
Sign up to set email alerts
|

HIV Disclosure and Transmission Risks to Sex Partners Among HIV-Positive Men

Abstract: Disclosure of HIV-positive status to sex partners is critical to protecting uninfected partners. In addition, people living with HIV often risk criminal prosecution when they do not inform sex partners of their HIV status. The current study examined factors associated with nondisclosure of HIV status by men living with HIV in Atlanta, GA (92% African African, mean age = 43.8), who engage in condomless sex with uninfected sex partners. Sexually active HIV-positive men (N = 538) completed daily electronic sexual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 43 publications
1
26
0
Order By: Relevance
“…It was shown that majority of BBRs had multiple sexual relationships including those with regular sexual partners (apart from their spouses or permanent girlfriends) and only few of them (~37%) used condoms during sex. The act of having multiple sexual partners and the reckless behaviour of not using condom during sexual relationships may increases the risk of getting HIV infection as previously described [28,29]. Moreover, our study reported that about 23% and 11.5% of all BBRs had had sexual relationships with causal and commercial partners, respectively; but majority of these (>62%) used condoms during their encounters.…”
Section: Discussionsupporting
confidence: 68%
“…It was shown that majority of BBRs had multiple sexual relationships including those with regular sexual partners (apart from their spouses or permanent girlfriends) and only few of them (~37%) used condoms during sex. The act of having multiple sexual partners and the reckless behaviour of not using condom during sexual relationships may increases the risk of getting HIV infection as previously described [28,29]. Moreover, our study reported that about 23% and 11.5% of all BBRs had had sexual relationships with causal and commercial partners, respectively; but majority of these (>62%) used condoms during their encounters.…”
Section: Discussionsupporting
confidence: 68%
“…Self-disclosure plays an important role in stemming HIV transmission and enhancing HIV prevention and treatment (1, 2). Disclosing HIV serostatus to others helps people living with HIV (PLH) garner greater tangible and emotional social support and helps them obtain better health care and counseling services (3-5).…”
Section: Introductionmentioning
confidence: 99%
“…Kalichman et al (2016), in their study, with 538 sexually active HIV+ men found that undisclosed HIV+ status was common and associated with unprotected sex with uninfected partners and less adherence to care. Thus, interventions are needed that enhance disclosure self-efficacy, and increase understanding of HIV infectiousness (Kalichman et al, 2016). The relationship-level interventions, therefore, must focus on promoting healthy relationships, addressing IPV, building healthy communication including condom negotiation skills and skills in identifying and addressing risks associated with a high-risk partner.…”
Section: Discussionmentioning
confidence: 94%
“…Disclosure of HIV+ status to a sexual partner is critical for HIV prevention (Kalichman, Kalichman, Cherry, & Grebler, 2016). Kalichman et al (2016), in their study, with 538 sexually active HIV+ men found that undisclosed HIV+ status was common and associated with unprotected sex with uninfected partners and less adherence to care. Thus, interventions are needed that enhance disclosure self-efficacy, and increase understanding of HIV infectiousness (Kalichman et al, 2016).…”
Section: Discussionmentioning
confidence: 99%